Energy conservation and planning - guidelines for energy efficient residential developments - Ho, Chin Siong (2006)
Since the Agenda 21 in the Rio summit, Energy efficiency has been recognized as an important consideration in designing building. There is also a growing interest in understanding energy efficient in the planning of city and even at regional level (Breheny, 1992; Nijkamp P. and Perrels A, 1994). This trend is observed in thec developed nations where apart from institutional research work, the NGOs and legislation on energy conservation (Energy Act 2004, Sustainable Energy Act 2003, Energy Conservation Act 1996), are also being enforced. Many of the recent publications tend to refer to energy conservation and energy efficient in the discussion of sustainable development. However, many of the developing countries including Malaysia still lack of research in the field of energy efficiency and its application in urban planning. The energy saving may be more substantial if the energy conservation ideas are incorporated at the earlier stage of planning at regional, city or neighbourhood levels. Hence it is important for the Federal Town and Country Planning department to develop energy efficient guidelines for the local planning authorities to implement. It is the purpose of this paper to examine the current literature on this subject and finally outline broad energy efficient guidelines to relevant authorities such as Federal Town and Country Planning Department and local authorities to consider the aspects of energy conservation into their strategic and physical planning. It is hope that some of the proposals may play the roles as guidelines for planning practitioners at neighbourhood or city level. This paper will focus more at neighbourhood and city levels. The author also recognises that energy efficient home features at building level, should include building orientation, internal room, layout, insulation, ventilation, heat proofing and use of energy efficient appliances.